Study of the microbial mobilization of phosphates in the soil by percolation - Ramos, A.; Callao, V. (Ars Pharmaceutica (Internet), 1967)
In the present work, the possible increase in the mobilization of phosphorus by a Bacillus sp. Is studied by the percolation technique. which uses glycerophosphate. The results obtained in inoculated and uninoculated soil were similar, however an increase in soluble phosphorus content after the addition of calcium glycerophosphate could be observed. It also exposes the difficulties and disadvantages that must be saved for a proper functioning of the method.